CONFIRMATION OF HIGH TEMPERATURE STRONGLY PERALUMINOUS MAYIN'EBO GRANITES IN THE SOUTH MARGIN OF ALTAY, XINJIANG: AGE, GEOCHEMISTRY AND TECTONIC IMPLICATIONS - Zhou G.; Yin L.J.; Luo S.B.; He B.; Wang X.; Zhao H.; Li A.H.; He Y.K.; Zhang Z.C. (My University, 2007)
Mayin'ebo pluton, outcropping at the northeastern side of Mayin'ebo Fault, is comprised of gneissic tonalite, granodiorite, and granite. Some Al-riched diagnostic minerals, such sillimanite, cordierite, tourmaline, have been observed in this pluton, which is coherent with their high A/CNK values (> 1.1). Zircon SHRIMP U-Pb dating indicate it crystallized at ca. 283Ma. It has low SiO2, CaO, Ba, Sr, Nb, P2O5 and relatively high but variable MgO, FeOT, Cr, Ni, TiO2, REE (∑ REE = 126.8 × 10-6 - 218.11 × 10-6). It is characterized by enrichment of LREE with (La/Yb)N ranging from 5 to 11 and mediate negative Eu anomalies (δEu=0.52-0.74). Petrography and chemical composition of the Mayin'ebo granites share characteristics of the typical peraluminous granites. Due to their low Al2O3/TiO2 ratios, it belong high-temperature sub-type of the peraluminous granites. On the other hand, the granites have negative but large-ranged initial Nd values (-0.3 - -3.5). Considering the gabbro with positive initial Nd values (+ 5) mingling in the granites, we suggest that the Mayin'ebo granite was derived from partial melting of the psammitic rocks with low maturity induced by underplating of the mafic magma from a depleted mantle, and to some extent, the mafic magma has been added into the primary magma of the granite. In combination with previous studies, we concluded that the Mayin'bo granites was formed in an extensional post-orogenic environment. This study provides an important petrogenetic type of post-collision granites in Altay and even in the Center Asian Orogen Belt.
Keywords: AGE; ALTAY; GEOCHEMISTRY; PERMIAN STRONGLY PERALUMINOUS GRANITES; TECTONIC IMPLICATIONS; Paleozoic::Permian::Cisuralian; Палеозой::Пермская::Приуральский::Кунгурский